Trends in renewable energy production employing biomass-based biochar. (November 2021) - Kant Bhatia, Shashi; Palai, Akshaya K.; Kumar, Amit; Kant Bhatia, Ravi; Kumar Patel, Anil; Kumar Thakur, Vijay; Yang, Yung-Hun
Graphical abstract: Highlights: Renewable energy seems a promising approach to fulfill the future energy demand. Biochar is an economic, and efficient material for energy production. It can be utilized for electrode preparation used in MFC. Biochar is also used as a catalyst for biodiesel and hydrogen production. Need to work on technology for biochar synthesis with desired properties. Abstract: Tremendous population growth and industrialization have increased energy consumption unprecedentedly. The depletion of fossil-based energy supplies necessitates the exploration of solar, geothermal, wind, hydrogen, biodiesel, etc. as a clean and renewable energy source. Most of these energy sources are intermittent, while bioelectricity, biodiesel, and biohydrogen can be produced using abundantly available organic wastes regularly. The production of various energy resources requires materials that are costly and affect the applicability at a large scale. Biomass-derived materials (biochar) are getting attention in the field of bioenergy due to their simple method of synthesis, high surface area, porosity, and availability of functional groups for easy modification. Biochar synthesis using various techniques is discussed and their use as an electrode (anodic/cathodic) in a microbial fuel cell (MFC), catalysts in transesterification, and anaerobic digestion for energy production are reviewed. Renewable energy production using biochar would be a sustainable approach to create an energy secure world.